SARS-CoV-2 infection: use and effectiveness of antigenic swab for the health surveillance of healthcare workers - Coggiola, Maurizio; Cavallo, Rossana; Grillo, Eugenio; Frammartino, Roberto; Clemente, Giuseppe; Costa, Cristina; Raciti, Ida Marina; Silvestre, Carlo; Scozzari, Gitana; Paradisi, Ettore; Tuffanelli, Alessandro; Alfonso Pensamiento, Maria Carolina; et al. (La Medicina del Lavoro, 2021)
Background: The gold standard to identify SARS-CoV-2 infections is the Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) on rhino-pharyngeal swabs, but faster and cheaper methods such as antigenic swabs have been developed. A retrospective observational study on antigenic swabs included in the extraordinary health surveillance protocol of a large Hospital in Turin was aimed to assess their performance validity. Methods: From 30 October 2020 to 4 May 2021, 4000 antigenic swabs were carried out in three groups of healthcare workers (HCWs), respectively (i) asymptomatic, (ii) cohabiting with a positive case, and (iii) not recently exposed to the virus. Results: Overall sensitivity and specificity associated with a prevalence of 1.30% were 26.9%, 97.2%, respectively, the corresponding positive (PPV) and negative predictive value (NPV) being 11.29% and 99.02% [95% IC (99.00 - 99.04)] respectively; a prevalence of 0.29% was observed in the asymptomatic group, among whom sensitivity and specificity were 25.0% and 98.9%, respectively, the corresponding PPV and NPV being 6.25% and 99.78% [95% IC (99.76 - 99.81)], respectively; the cohabitant group showed a prevalence of 21.11%, sensitivity and specificity were 47.4%, 81.7%, respectively, giving rise to a PPV of 40.91% and NPV of 85.29% [95% IC (85.18 – 85.41)] respectively. The prevalence in the not exposed group was 0.77%, sensitivity and specificity were 29.2%, 97.4%, respectively, and PPV and NPV 8.05% and 99.44% [95% IC (99.42 - 99.46)] respectively. Conclusions: Antigenic swabs reduced costs and provided reliable diagnostic results. In the cohabitant group, the higher-prevalence groups showed poor test performances, likely because of the high prevalence of pre-symptomatic illness in this group. Owing to the relatively low NPV, a negative result would still require confirmation with a molecular test to be acceptable for a surveillance program that effectively reduces the virus’s intra-hospital spread.